Assessment of the Ecological Impact of Pollution in the Damanganga River - Godhaniya, Manoj; Antaliya, Komal; Patel, Rajesh; Kothari, Charmy (Acta Chimica Asiana, 2024)
The Damanganga River faces severe pollution from industrial effluents and sewage, impacting its ecological health. The study aimed to analyze the current water quality status at the proposed conventional barrage site across the river between Silvassa, Vapi and Daman in India. Water samples were collected from three sites along the river during different seasons and analyzed for physicochemical parameters like TDS, COD, BOD, nutrients, fecal coliforms, heavy metals, etc. as per standard methods. Principal component analysis (PCA) was done. GCMS profiling of organics was also carried out. Several parameters exceeded the desired limits. TDS, BOD, fecal coliforms were very high indicating organic pollution and sewage contamination. Dissolved oxygen was deficient at some sites. Cadmium, copper and iron exceeded limits due to industrial releases containing these metals. PCA showed organic pollution as the major degrading factor for water quality followed by industrial contamination. GCMS analysis revealed hazardous organics like petrochemicals, fatty acids, solvents, pesticides and aromatic pollutants at varying levels along the river’s course demonstrating pollution from oil spillages, industrial effluents and agricultural runoff. The findings confirm severe deterioration in the Damanganga's water quality from inadequately treated sewage and industrial discharges posing environmental and health risks. Stringent regulations, proper wastewater treatment, runoff control and regular monitoring are vital to improve the river's condition